English Speaking Achievement and Environmental Conscientization by Using Think-Pair- Share Strategy - Jenny Elvinna Manurung; Nita Ria (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2018)
The objective of the study was to describe the implication of speaking achievement and Environmental Conscientization by Using Think-Pair-Share to Senior High School Students of Methodist 2 Palembang. Thirty-two people ofSenior High School Students of Methodist 2 Palembang became the sample of the study. The writer used a classroom action research as a method of study. This study consisted of two cycles; cycle I and cycle II. Test and observation were used to collect the data. Data calculation showed that there was a significant improvement on students' speaking achievement and environmental conscientization, the mean score of speaking achievement in cycle I was 57,63 with learning completeness 15,63% and its environmental conscientization was 56. Then, the mean score of speaking achievement in cycle II was 77 with learning completeness 84,38%and it's environmental conscientization was 74. In other words, speaking achievement and local cultural awareness was improved by using think-pair-share. Besides, the students' perception toward the implementation of think pair share was good.